THE STRATEGIES FOR IMPROVING DEBATING SKILLS. - Jessica Jessica; Endang Susilawati; Surmiyati Surmiyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This research was aimed to describe the strategies for improving debating skills. The subject of this research were the English debate competition participant at EESP of Universitas Tanjungpura Pontianak. This research used a case study approach and data were collected from interviews and related documents including student certificate in debate. In this research, the researcher focused on two aspects that contribute to student strategies in debating. The first aspect was about the strategies for matter. Referring to the first aspect the results are the strategies to define the motion, implement AREL (Assertion, Reasoning, Evidence, and Link-back), create the theme line, find the weak point of argument from opponent teams and do the POI. The second aspect was about the strategies for manner. Referring to the second aspect the results are the strategies to control the voice, body language, and language while deliver the speech.